A wheat cysteine-rich receptor-like kinase confers broad-spectrum resistance against Septoria tritici blotch - Cyrille Saintenac; Florence Cambon; Lamia Aouini; Els Verstappen; Seyed Mahmoud Tabib Ghaffary; Théo Poucet; William Marande; Hélène Berges; Steven Xu; Maëlle Jaouannet; Bruno Favery; Julien Alassimone; et al. (Nature Communications, 2021)
Septoria tritici blotch (STB) is a devastating foliar disease affecting worldwide wheat production. Here, the authors report a cysteine-rich receptor-like kinase that can confer resistance to Zymoseptoria tritici, the pathogen that causes STB, and slow penetration and intercellular growth of the pathogen.